The Impact of Culture on Accounting Choices: Can Cultural Conservatism Explain Accounting Conservatism? - Kang, Tony (Institutional Knowledge at Singapore Management University, 2004)
We explore the extent to which cultural conservatism explains accounting conservatism. Our primary measure for accounting conservatism is the magnitude of non-operating accruals, which are highly discretionary in nature. Culture permeates values and attitudes, and thus governs many aspects of human behavior. Hence it is likely to affect managers’ accounting choice behaviors. However, there is surprisingly little evidence on the association between the two types of conservatism in the literature. Using a sample of 800 firms originating from 21 countries during the nine-year period from 1993 to 2001, we find strong evidence that the managers in more conservative cultural environments tend to make more conservative accounting choices (e.g., report lower estimates for future cash flows). We also find some empirical support for the idea that culture and legal regime interact as substitutes in explaining accounting conservatism.